Pengaruh Pembangunan Pertanian terhadap Pertumbuhan Ekonomi Indonesia Tahun 1985-2022 - Sanjaya, Muhammad Yeka; Hadiyanto, Handoko (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
This quantitative research aims to determine the short and long-term relationship between agricultural development and economic growth in Indonesia from 1985-2022. It employed the ECM (Error Correction Model) method. The data involved secondary data from 1985-2022 collected from the official website of the World Bank. There were two variables in this research: Economic Growth and Agricultural Development. Economic growth data were based on constant prices in Indonesia for 1985-2022 from the World Bank website. The data was manifested in percent. The second variable was agricultural development, namely agriculture, forestry, and fisheries. It referred to ISIC divisions 1-3 and included forestry, hunting, and fisheries, as well as food crop cultivation and livestock production. Agricultural development data covering 1985-2022 was gathered from the World Bank website. The data was shown in percent. The results indicated that the agricultural development variable had a short-term effect on economic growth in Indonesia. The ECT coefficient was significant in the short term but had a negative relationship. Thus, the correlation was negative. Meanwhile, the long-term relationship between agricultural development and economic growth did not show a significant effect. Agricultural development variables had a long-term negative effect on economic growth in Indonesia. This research is hoped to provide new information and discussions that are in line with the analysis of the influence of agricultural development on economic growth in Indonesia. In addition, it can share the views of the Indonesian government in formulating policies regarding the analysis of agricultural development in Indonesia.